Intervenciones de enfermería en la prevención del dengue en adultos atendidos en el Centro de Salud Montalvo en el periodo noviembre 2023- marzo 2024. - Mero Rivas, Yomaira Patricia (2024)
Dengue is a virus that is commonly found in tropical areas and its presence is related to factors such as rainfall, temperature, urbanization, and the presence of its main mosquito vector, Aedes aegypti. The global burden of this disease is unknown, but its epidemiological patterns are worrying for humans, health, and the global economy. Dengue is predicted as a future disease due to increasing urbanization, lack of water and possibly environmental change. This virus is mainly transmitted in the Eastern Mediterranean, America, Southeast Asia, Western Pacific, and Africa. With the dengue genome, its behavior can be predicted. The development of medicinal compounds and choices in medical practice depend on understanding the genetic aspects of the virus to evaluate its harmful potential. For this reason, the current study aims to determine nursing interventions and their influence on the prevention of dengue in adults treated at the Montalvo Health Center in the period November 2023-March 2024. The methodology applied was quantitative, descriptive. and documentary; A sample of 80 adults who are treated at the Montalvo Health Center in the period November 2023-March 2024 was obtained.